The Impact of Online Hearings on The Enforcement of Arbitral Awards - Ceyda Süral Efeçınar; Zeynep Derya Tarman (Annales de la Faculté de Droit d’Istanbul)
Due to the flexible nature of arbitration, it was possible to continue arbitral proceedings through online hearings during the global Covid-19 pandemic. The immense use of online hearings during these tough times forced arbitral institutions to provide certain guidelines and principles regarding the organization of online hearings. Meanwhile, arbitration community figured out the advantages and efficiency of online hearings. Along with the rapid increase of energy prices, inflation rates and climate change concerns, we believe that online hearings will continue to be an indispensable part of international arbitration practice in the future. However, despite being cost and time effective, online hearings raise discussions in the context of the right to a fair trial, the right to be heard and the principle of equality of the parties provided by Article 6 of the European Convention on Human Rights and by Article 36 of the Turkish Constitution. In our study, we will examine whether online hearings per se will be considered as an infringement of the right to a fair trial in the light of recent decisions of the Turkish Constitutional Court evaluating the use of online hearings in court practice. We will try to make conclusions whether and/or under which circumstances the use of online hearings will constitute a ground of setting aside under the Turkish International Arbitration Act or denial of recognition or enforcement according to the New York Convention.